Challenges on Mercury's Interior Structure Posed by the New Measurements of its Obliquity and Tides. Issue 3 (7th February 2021) - Steinbrügge, G.; Dumberry, M.; Rivoldini, A.; Schubert, G.; Cao, H.; Schroeder, D. M.; Soderlund, K. M.
Abstract: We present calculations of interior models of Mercury that are constrained to match Mercury's mean density, normalized moment of inertia factor (MoI), and 88 days libration amplitude. We show that models matching a MoI = 0.333 ± 0.005, based on a recent obliquity measurement require a new perspective on Mercury's interior. Specifically, we confirm the mandatory presence of a large inner core > 600 km in radius which, however, leads to lower mantle densities in comparison to previous models and implies a mantle with > 5wt.% C, > 10wt.% magnesium sulfide (MgS), or is partially convecting. Furthermore, we also show that the core radius is lower than previous estimates, making it inconsistent with current estimates from magnetic induction measurements. In addition, the requirement of low viscosities in the lower mantle to match recent estimates of k 2 imply a significantly weaker mantle than previously believed, potentially including partial melting. Plain Language Summary: The precise orientation of Mercury's axis of rotation in space (the obliquity) depends on the planet's moment of inertia (MoI). The MoI gives a measure of the radial distribution of mass in the interior of a planet. Here, we construct models of the interior of Mercury that match MoI values that have been deduced from observations of its rotational state. We show that models that match the MoI based on a recent obliquity measurement force a new perspective on Mercury's interior structure. In particular, they feature a large solid inner core, a mantle density which is lower compared to that expected of typical terrestrial planets implying a different composition with more light elements included into Mercury's mantle. Interior models also feature a warmer core and a warmer mantle which places new constraints on how Mercury evolved and how melting has led to volcanism in its past. Key Points: We present calculations of Mercury interior models constrained to match its normalized polar moment of inertia (MoI) We confirm that models matching a MoI = 0.333 ± 0.005 require large inner core sizes The new constraints imply a lower mantle density and a higher core temperature